2014
DOI: 10.5306/wjco.v5.i3.283
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis, prevention, diagnosis and treatment of breast cancer

Abstract: Breast cancer is the most common cancer affecting women worldwide. Prediction models stratify a woman's risk for developing cancer and can guide screening recommendations based on the presence of known and quantifiable hormonal, environmental, personal, or genetic risk factors. Mammography remains the mainstay breast cancer screening and detection but magnetic resonance imaging and ultrasound have become useful diagnostic adjuncts in select patient populations. The management of breast cancer has seen much ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
176
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(206 citation statements)
references
References 113 publications
(128 reference statements)
1
176
0
12
Order By: Relevance
“…( [1][2][3][4][5][6][7] Strategies to control the disease in Brazil have been implemented since the latter part of the last century, and they are characterized by isolated actions. In 2004, these actions become systematized in programs whose goal is to reduce breast cancer mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…( [1][2][3][4][5][6][7] Strategies to control the disease in Brazil have been implemented since the latter part of the last century, and they are characterized by isolated actions. In 2004, these actions become systematized in programs whose goal is to reduce breast cancer mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common malignancy occurring in females from Western countries (1). In Brazil, it has been estimated that 57,960 new cases and 14,207 deaths due to the disease will occur in 2016 (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…1 Although the majority of patients are offered breast conservation therapy, audit data from the Royal College of Surgeons in the UK in 2009 showed that around 40% of patients still undergo mastectomy. 2 More recently, analysis of trends in Europe shows a decline in mastectomy rates from the period 2005-2010 by 4% a year, to the current rate of ,20% a year.…”
Section: Introductionmentioning
confidence: 99%